2017
DOI: 10.1002/jwmg.21328
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence for declines in muskrat populations across the United States

Abstract: Muskrats (Ondatra zibethicus) are native to North America and widely distributed across the continent. Recent evidence and anecdotal reports suggest that muskrat populations may be declining; however, this assumption has not been rigorously evaluated. We used 42 years of muskrat harvest data (1970–2012) from 37 states to examine trends in muskrat populations across the United States. Annual harvest data are highly correlated with annual pelt prices, which must be controlled for prior to analysis. After adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Pelt price, in particular, has been used widely as an indicator of trapper effort in studies of harvest trends in multiple furbearer species [33,35,36]. In a recent range-wide analysis of muskrat (Ondatra zibethicus) harvest where pelt price was only occasionally reported by states, Ahlers & Heske [37] found that pelt price was similar across localities and thus an average value could be applied to all states and provinces to correct for trapping effort. We converted Canadian weasel pelt prices to US dollar amounts using a year-specific conversion rate and corrected the pelt price for inflation using the Consumer Price Index (CPI; www.bls.gov/data/) adjusted to 2017 US dollar values.…”
Section: Plos Onementioning
confidence: 99%
“…Pelt price, in particular, has been used widely as an indicator of trapper effort in studies of harvest trends in multiple furbearer species [33,35,36]. In a recent range-wide analysis of muskrat (Ondatra zibethicus) harvest where pelt price was only occasionally reported by states, Ahlers & Heske [37] found that pelt price was similar across localities and thus an average value could be applied to all states and provinces to correct for trapping effort. We converted Canadian weasel pelt prices to US dollar amounts using a year-specific conversion rate and corrected the pelt price for inflation using the Consumer Price Index (CPI; www.bls.gov/data/) adjusted to 2017 US dollar values.…”
Section: Plos Onementioning
confidence: 99%
“…However, robust empirical data on long-term trends in muskrat populations based on field observations are generally scarce in the literature. Thus, more information is needed to confirm that declines in muskrat harvest correspond to real declines in muskrat abundance (Ahlers and Heske, 2017). Fortunately, we learned of annual muskrat field surveys having been conducted at multiple locations in Ontario, Canada between 1950 and and sought to exploit this untapped source of historic muskrat population data.…”
Section: Introductionmentioning
confidence: 99%
“…Muskrats Ondatra zibethicus are ecologically and economically important semi‐aquatic mammals whose populations appear to be declining throughout their native range in North America (Roberts & Crimmins 2010, Ahlers & Heske 2017, Greenhorn et al 2017, Gregory et al 2019). They are also an invasive species in Europe, South America, and Asia (Anderson et al 2006, Xu et al 2006).…”
Section: Introductionmentioning
confidence: 99%